2003
DOI: 10.1080/07448480309595732
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Men as Social Justice Allies in Ending Violence Against Women: Evidence for a Social Norms Approach

Abstract: The field of sexual assault prevention is shifting attention to educational interventions that address the role of men in ending violence against women. Recent studies document the often-misperceived norms men hold about other men's endorsement of rape-supportive attitudes and behaviors. The authors provide further evidence supporting the design of population-based social norms interventions to prevent sexual assault. Data from this study suggest that men underestimate the importance that most men and women pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
294
3
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(315 citation statements)
references
References 17 publications
6
294
3
3
Order By: Relevance
“…Research has shown that peer norms are a powerful predictor of bystander attitudes, with people reporting that they are significantly less likely to intervene if they perceive it would be a violation of their peer norms (Burn, 2009;Fabiano et al, 2003;Latane & Darley, 1968). Research indicates that regardless of gender, individuals are less likely to intervene if they perceive that their peers would not be supportive (Rutkowski, Gruder, & Romer, 1983;Schwartz & Gottlieb, 1980); however, this effect is particularly pronounced for men.…”
Section: Bystander Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that peer norms are a powerful predictor of bystander attitudes, with people reporting that they are significantly less likely to intervene if they perceive it would be a violation of their peer norms (Burn, 2009;Fabiano et al, 2003;Latane & Darley, 1968). Research indicates that regardless of gender, individuals are less likely to intervene if they perceive that their peers would not be supportive (Rutkowski, Gruder, & Romer, 1983;Schwartz & Gottlieb, 1980); however, this effect is particularly pronounced for men.…”
Section: Bystander Interventionmentioning
confidence: 99%
“…Research indicates that regardless of gender, individuals are less likely to intervene if they perceive that their peers would not be supportive (Rutkowski, Gruder, & Romer, 1983;Schwartz & Gottlieb, 1980); however, this effect is particularly pronounced for men. Two studies of college men found that the most significant predictor of their willingness to intervene was their perception of whether or not their peers would be willing to act (Brown & Messman-Moore, 2010;Fabiano et al, 2003). So, how do peer norms in Greek organizations impact fraternity men and sorority women's likelihood of intervening?…”
Section: Bystander Interventionmentioning
confidence: 99%
“…In a qualitative study examining men's intentions to intervene in three written scenarios, Carlson (2008) found that the most common reason men stated for failing to intervene was evaluation apprehension, they did not want to appear weak to other men. In another study, Fabiano, Perkins, Berkowitz, Linkenback, and Stark (2003) found that the best predictor of men's willingness to intervene was their perception of other men's willingness to intervene. Two recent studies have specifically examined the differential influence of an individual's attitudes and their perceptions of others' attitudes on their intentions to engage in prosocial bystander behavior.…”
Section: Social Norms Theorymentioning
confidence: 99%
“…For example, willingness or intentions to intervene has been used as a proxy for men's intervention behavior (Brown & Messman-Moore, 2010;Fabiano et al, 2003;Stein, 2007). Intentions have been posited to play a key role in the prediction of behavior, and have been highlighted in a number of models relating attitudes and behaviors, including the theory of reasoned action (Ajzen & Fishbein, 1980;Fishbein & Ajzen, 1975) and the theory of planned behavior (Ajzen, 1985).…”
Section: Social Norms Theorymentioning
confidence: 99%
“…Research indicates that people frequently misperceive, and overestimate their peer's beliefs and attitudes with regards to a variety of high risk and sexual behaviors (Scholly, Katz, Gascoigne, & Holck, 2005) and that men often overestimate other men's adherence to sexist beliefs and attitudes that promote sexual aggression (Fabiano, Perkins, Berkowitz, Linkenbach, & Stark, 2003). Further, research has demonstrated that hypermasculine environments are more conducive to sexually aggressive behavior (Humphrey & Kahn, 2000) and that men are more likely to engage in sexually aggressive behavior when they receive support for the behavior from their peers (DeKeseredy & Kelly, 1995).…”
Section: Groupmentioning
confidence: 99%